The psychological impact of first-time childbirth on parents - Bo Zhu; Yani Guo; Meng Du; Xiangjun Zhou (PLoS ONE, 2026)
The psychological effects of first-time childbirth on parents have long been a focal point in social science research. This study provides a new perspective by applying demographic transition theory to explore how the experience of having a first child influences parents’ mental health. Our findings indicate that the arrival of a first child not only increases family size but also brings about significant psychological and emotional adjustments in parents. These changes are often driven by pressures associated with financial stability, career development, and shifts in personal identity, which prompt parents to reconsider their life goals and values. Moreover, the psychological effects of first-time childbirth vary notably across different socioeconomic backgrounds. This paper offers empirical insights that can guide policymakers and social organizations in developing targeted support and intervention strategies to enhance parental well-being during the transition to parenthood.